Budaya Birokrasi Untuk Perbaikan Pelayanan Publik - Andriansyah Andriansyah; Deni Nurdyana Hamidin; Meti Nurhayati (Public Administration Journal (PAJ), 2017)
Decentralization of the government has brought wide implication of political reform. Democracy and decentralization expected to become the gateway to achieve Indonesian prosperity of society in all aspect. Through decentralization, bureaucracy is expected to be able to develop more humanistic mindset and culture so that policy formulation becomes more aware for society prosperity. Bureaucratic reform also becomes the right moment to conduct the reconstruction of culture pattern in organizational system. Reconstruction of the bureaucracy culture will touch the basic dimension which is reformation of public service delivery has affected the improvement of social prosperity in all aspectDecentralization of the government hasbrought wide implication of political reform.Democracy and decentralization expected tobecome the gateway to achieve Indonesianprosperity of society in all aspect. Throughdecentralization, bureaucracy is expected to beable to develop more humanistic mindset andculture so that policy formulation becomes moreaware for society prosperity. Bureaucratic reformalso becomes the right moment to conduct thereconstruction of culture pattern in organizationalsystem. Reconstruction of the bureaucracyculture will touch the basic dimension which isreformation of public service delivery has affectedthe improvement of social prosperity in all aspect